2021
DOI: 10.1111/myc.13216
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of galactomannan testing on tracheal aspirates in COVID‐19‐associated pulmonary aspergillosis

Abstract: Objective Our aim was to evaluate the performance of two galactomannan assays (Platelia Aspergillus EIA, BioRadⓇ, and Aspergillus Galactomannan LFA, IMMYⓇ, Norman, OK, USA) in tracheal aspirate (TA) samples of consecutive critically ill patients with COVID‐19. Methods We included critically ill patients, performed GM‐EIA and GM‐LFA in TA and followed them until development of CAPA or alternate diagnosis. CAPA was defined according to the modified AspICU cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
2
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(77 citation statements)
references
References 30 publications
(76 reference statements)
1
72
2
2
Order By: Relevance
“…A single-center, retrospective study by Roman-Montes et al revealed the incidence of putative CAPA at 9.7% in 144 patients using the modified AspICU-Dutch/Belgian Mycosis Study Group criteria. [ 27 ] Respiratory tract cultures were obtained if clinical status worsens during ICU admission. Finally, the largest study was a prospective single-center cohort by Machado et al with an incidence of putative CAPA at 2.5% in 239 patients using the modified AspICU-Dutch/Belgian Mycosis Study Group criteria.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A single-center, retrospective study by Roman-Montes et al revealed the incidence of putative CAPA at 9.7% in 144 patients using the modified AspICU-Dutch/Belgian Mycosis Study Group criteria. [ 27 ] Respiratory tract cultures were obtained if clinical status worsens during ICU admission. Finally, the largest study was a prospective single-center cohort by Machado et al with an incidence of putative CAPA at 2.5% in 239 patients using the modified AspICU-Dutch/Belgian Mycosis Study Group criteria.…”
Section: Resultsmentioning
confidence: 99%
“…[ 15 ] It is important to note that Roman-Montes et al used GM obtained from ETA as an equivalent for BAL GM, whereas studies by Dupont et al and Lamoth et al used bronchial aspirates (BAS) as an equivalent for BAL in assisting with diagnosis of putative CAPA due to concerns of exposure and transmission associated with bronchoscopy. [ 27 , 42 , 43 ]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Denmark, 10 a 25% ( n = 2/8) incidence of invasive aspergillosis in COVID‐19 patients undergoing extracorporeal membrane oxygenation (ECMO) was described, totalling 7.4% when adding the non‐ECMO ICU population ( n = 19). China, 11 Mexico 12 and Switzerland 13 report incidences of 8%, 9.7% and 3.8% in mechanically ventilated patients, respectively. In addition, Spain 14 and Pakistan 15 reported CAPA incidences of 3.3% and 21.7% in single studies, respectively, although patient data describing the use of mechanical ventilation were incomplete.…”
Section: Introductionmentioning
confidence: 99%